2018
DOI: 10.1017/s0272263117000316
|View full text |Cite
|
Sign up to set email alerts
|

Observing Pitch Gestures Favors the Learning of Spanish Intonation by Mandarin Speakers

Abstract: Recent studies on the learning of L2 prosody have suggested that pitch gestures can enhance the learning of the L2 lexical tones. Yet it remains unclear whether the use of these gestures can aid the learning of L2 intonation, especially by tonal-language speakers. Sixty-four Mandarin speakers with basic-level Spanish were asked to learn three Spanish intonation patterns, all involving a low tone on the nuclear accent. In a pre-post test experimental design, half of the participants received intonation training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…The results of our study add more evidence in favor of the benefits of pitch gestures for learning L2 tones and intonation (Hannah et al, 2016;Kelly et al, 2017;Morett & Chang 2015;Yuan et al, 2018). Specifically, our results partially replicate and extend the findings by Morett and Chang (2015).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of our study add more evidence in favor of the benefits of pitch gestures for learning L2 tones and intonation (Hannah et al, 2016;Kelly et al, 2017;Morett & Chang 2015;Yuan et al, 2018). Specifically, our results partially replicate and extend the findings by Morett and Chang (2015).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast with the positive results obtained in various studies on the role of pitch gestures on the acquisition of second language tones or intonation (Hannah et al, 2016; Kelly et al, 2017; Morett & Chang, 2015; Yuan et al, 2018), there is to date no clear view on how other types of metaphoric (and beat) gestures affect phonological learning. In contrast with the positive effects of pitch gestures for learning L2 tones and intonation, the results of studies targeting the effectiveness of what are called “length gestures” to learn duration contrasts in a second language are not so clear.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, the fact that we found the effect at the time of the delayed posttest speaks to memory‐enhancing effects of multimodal encoding (dual‐coding theory; Paivio, 1991; Paivio & Desrochers, 1980, and the enactment effect; Engelkamp & Dehn, 2000). Therefore, this study suggests that the memory‐enhancing effect of gestures, which has been found in the domain of vocabulary (e.g., Huang et al., 2019; Kelly et al., 2009; Tellier, 2008), and more recently, in grammar (Nakatsukasa, 2016) and suprasegmental features of speech (e.g., Yuan et al., 2019), might reach the segmental phonology level of L2 acquisition. However, this interpretation must be treated with caution.…”
Section: Discussionmentioning
confidence: 56%
“…Zhang, Baills, and Prieto (2018), for example, found that Chinese monolinguals learned the rhythmic patterns of French words better through the use of handclapping. Metaphoric pitch gestures (Yuan, González‐Fuente, Baills, & Prieto, 2019) and rhythmic beat gestures (Gluhareva & Prieto, 2017) have also been reported to help L2 learners improve intonation patterns in Spanish and accentedness in English, respectively. Therefore, when it comes to suprasegmentals, both observational and experimental studies have seemed to suggest that gestures are useful for L2 pronunciation instruction.…”
Section: Background Literaturementioning
confidence: 99%